Study of Hybrid Wind and Solar Energy Power Plants: An Analysis of the Battery Charging and Discharging System - Sumarno, F Gatot; Evan, Bah; Aspriyanti, Vita Ayu; Alwi, Muhammad (Politeknik Negeri Semarang, 2025)
Alternative energy can address the issue of PLN electricity supply, which is not available in all regions of Indonesia. The hybrid system of solar cells and wind turbines is a clean and environmentally friendly energy source because it does not produce carbon dioxide (CO₂) or other gases that play a role in global warming. The purpose of this final project is to analyze the length of time needed by a hybrid generator to charge and discharge the battery using load variations. This test was conducted in the Energy Conversion Laboratory using a unit of hybrid system equipment produced by KTENG (Korea Technology). The method employed involves charging the battery with energy generated from the hybrid system and discharging it using variations in lamp load. The results of this study indicate that the time needed to charge the battery is 21.28 hours in slightly cloudy weather with a total current of 4.7 amperes, and the battery discharge reaches 200 hours using a 10-watt load. Hybrid Generator, Battery Charging, and Discharging